2016
DOI: 10.1016/j.toxlet.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Mercury sulfides are much less nephrotoxic than mercury chloride and methylmercury in mice

Abstract: Mercury sulfides (α-HgS, β-HgS) are frequently included in traditional medicines. Mercury is known for nephrotoxicity, their safety is of concern. To address this question, mice were orally administrated with Zuotai (54% β-HgS, 30mg/kg), α-HgS (HgS, 30mg/kg), HgCl (33.6mg/kg), or MeHgCl (3.1mg/kg) for 7days, and nephrotoxicity was examined. Animal body weights were decreased by HgCl and to a lesser extent by MeHg, but unaltered after Zuotai and HgS. HgCl and MeHg produced renal tubular vacuolation, interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Brie y, 70W at 1 to 5-fold clinical doses and Zuotai (30 mg/kg, po) for 7 days did not produce signi cant effects on the liver CYP450 gene and protein expressions; while HgCl 2 at equivalent Hg dose increased the expression of CYP1A, CYP2B, CYP2E1, and CYP7A at the transcription and/or protein levels, MeHg at 1/10 Hg dose produced similar effects, but to a lesser extent. These results further demonstrated that chemical forms of metals are a major determinant of their biological effects [24][25][26][27][29][30][31].…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Brie y, 70W at 1 to 5-fold clinical doses and Zuotai (30 mg/kg, po) for 7 days did not produce signi cant effects on the liver CYP450 gene and protein expressions; while HgCl 2 at equivalent Hg dose increased the expression of CYP1A, CYP2B, CYP2E1, and CYP7A at the transcription and/or protein levels, MeHg at 1/10 Hg dose produced similar effects, but to a lesser extent. These results further demonstrated that chemical forms of metals are a major determinant of their biological effects [24][25][26][27][29][30][31].…”
Section: Discussionmentioning
confidence: 63%
“…Mice were given oral administration for consecutive 7 days. The dose regimen selection was based on our prior publications [8,11,[24][25][26][27]. Livers were collected 24 h after the last dose and stored at -80°C prior to analysis.…”
Section: Animal Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Modern analytical methods show that Zuotai contains mainly β-HgS, and other trace elements (Li et al, 2015) . In experimental animals, Zuotai at 4.5fold of clinical dose (30 mg/kg) did not show overt toxicity towards the kidney and liver as compared to HgCl 2 (at equivalent Hg dose) or MeHg (at 1/10 Hg dose) (Lu et al, 2015). In a recent clinical trial, Zuotai-containing Danzuo did not show obvious adverse effects in patients under the clinical doses and duration of administration .…”
Section: Introductionmentioning
confidence: 90%